2023
DOI: 10.3390/ijms242015279
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Natural Strength: Lamiaceae Essential Oils and Nanotechnology in In Vitro and In Vivo Medical Research

Tomasz Kowalczyk,
Anna Merecz-Sadowska,
Mansour Ghorbanpour
et al.

Abstract: The Lamiaceae is one of the most important families in the production of essential oils known to have a wide spectrum of biological activity. Recent research has highlighted the dermatological capabilities of various Lamiaceae essential oils, which appear to offer potential in free radical scavenging and anti-inflammatory activity. Some have also been extensively studied for their tissue remodeling and wound-healing, anti-aging, anti-melanogenic, and anti-cancer properties. Certain Lamiaceae essential oils are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 144 publications
0
2
0
Order By: Relevance
“…Previous studies have explored the impact of extracts of Lamiaceae representatives on bacterial growth activity [ 40 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]; however, our literature review revealed that current research mainly focuses on the antibacterial properties of essential oils derived from Lamiaceae plants [ 12 , 50 , 60 , 61 , 62 ]. In our study, B. subtilis showed the highest susceptibility to the effects of Lamiaceae extracts, with H. officinalis and S. officinalis ethanolic and S. scardica methanolic extracts demonstrating the most potent growth-inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the impact of extracts of Lamiaceae representatives on bacterial growth activity [ 40 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]; however, our literature review revealed that current research mainly focuses on the antibacterial properties of essential oils derived from Lamiaceae plants [ 12 , 50 , 60 , 61 , 62 ]. In our study, B. subtilis showed the highest susceptibility to the effects of Lamiaceae extracts, with H. officinalis and S. officinalis ethanolic and S. scardica methanolic extracts demonstrating the most potent growth-inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Plant essential oils are the main source of aromatic plant odors, which are mainly derived from the roots, stems, leaves, and other organs of plants and have long been used in culinary and medical applications in the historical record [6]. With deeper research, it has been found that plant essential oils have excellent antioxidant activity, antimicrobial activity, and other biological activities [7], which are mainly derived from the constituents of plant essential oils, which are dominated by terpenes and phenyl terpenoids, of which monoterpenoids are the most common [8] and, thus, natural compounds have been incorporated into the study of natural antimicrobial substances. Among the many natural compounds, limonene, due to its widespread presence in the essential oils of various plants, such as Citrus bergamia, Citrus deliciosa, Montanoa quadrangularis, Juniperus oxycedrus, Citrus unshiu, and Bursera graveolens [9,10], and excellent bioactivity has been considered by researchers as a potential sustainable natural active compound [11,12].…”
Section: Introductionmentioning
confidence: 99%